Interest barrier and capital structure response - Stephan Alberternst; Caren Sureth-Sloane (Arbeitskreis Quantitative Steuerlehre (arqus), 2016)
The Organisation for Economic Co-Operation and Development (OECD) recently proposed an interest barrier to fight tax base erosion and profit shifting (BEPS). We use the introduction of such an interest deductibility restriction in Germany as a quasi-experiment and find significant corporate capital structure responses. Using single entity financial statements and a detailed matching approach, we find evidence that companies that are affected by the interest barrier reduce their leverage by 4.7 percentage points more than non-affected companies. The effects are stronger among non-financially constrained firms. Our results imply that interest barrier effects on capital structure have so far been heavily underestimated.
Older version: http://hdl.handle.net/10419/106659
Keywords: F34; H21; H24; 330; financing decisions; German tax reform; interest barrier; leverage